Coastline environment vulnerability index mapping in Alcoy, Cebu, Philippines implicatons for the management of coastlines - Floren, Jessie O. (University of the Philippines in the Visayas-Cebu College, 2006)
The Central Visayas Region has approximately 2,680 kilometers stretch of coastline and it is about 15% of the country's coastline. Eighty-two percent (82%) or 109 out of 132 municipalities/cities are located in the coastal areas. Ninety-one percent (91%) of the population in the region is in the coastal zone. Issues arising from uncontrolled development along the foreshore areas in Central Visayas are alarming. These are in the form of reclamation, beach resort construction and even improper use of engineering structures such as jetties, seawalls and wharves. These issues were not addressed due to the lack of an integrated coastal zone management plan. Decisions on management responses to coastal erosion can be aided by a baseline, which characterizes the key variables influencing the coastline. This study attempted to assess and classify the different human and physical constraints acting on the coastline of Alcoy, Cebu Province. The study utilized a variety of indicators to develop a baseline upon which coastline management decisions can be These variables explored physical parameters (erosion/deposition, lithology, morphology), biological (reef conditions) as well as human parameters (anthropogenic pressure, policy and planning and positive best practices) to assess the current sensitivity of the coastline of one coastal town (one management unit). Overall the shoreline of Alcoy was identified to be moderately vulnerable where 90.3% or 7.092 km of the shoreline is to be sensitive to the vriables acting upon it. The 9.1% or 0.712 km high vulnerability suggests that there is the need for a comprehensive implementation of shoreline management wise practices in the town.